De eeuwigheidsdimensie van het heil: Een verkenning vanuit de praktijk van missionaire pioniers - Velde, Dolf te (Theologia reformata, 2023)
To what extent is the traditional doctrine of salvation applicable and relevant to missionary communication in a secularized, Western context? This article explores experiences and insights from three missionary pioneers in the Protestant Church in the Netherlands,with a particular eye on the "eternity dimension" of salvation. While people feel uneasy with a classical understanding of predestination, atonement, and regeneration, new aspects of transcendence or eternity can be discovered in missionary situations. Both a secular audience and missionary workers need an awareness of God's eternal choice and his faithfulness as the foundation for our response to the Gospel. The interaction between systematic-theological reflection and practical experience leads to mutualenrichment, and deepens our understanding of God's unconditional love and grace in Christ